Preparation method of 3D printing molecular sieve catalyst, prepared 3D printing molecular sieve catalyst and application

Through 3D printing technology, ZSM-5 molecular sieve is grown on aluminosilicate ceramic support and nickel ions are loaded, which solves the problem of low accessibility of metal and molecular sieve activity centers in the prior art, and achieves high catalytic activity and low cost Molecular sieve catalyst preparation.

CN119488946AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311049648.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

In the existing metal-supported ZSM-5 molecular sieve catalysts, the accessibility between the metal and the molecular sieve activity center is not high, resulting in low catalytic activity.

Method used

The molecular sieve catalyst was prepared by 3D printing technology. By hydrothermal crystallization on the aluminosilicate ceramic support, ZSM-5 molecular sieve was directly grown, and nickel ions were loaded through impregnation of metal nickel salt solution to form a metal nickel-loaded 3D printed molecular sieve. catalyst.

Benefits of technology

It improves the accessibility of the molecular sieve to metal sites, enhances catalytic activity, and is simple in preparation process and low in cost, which is suitable for catalytic cracking reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488946A_ABST
    Figure CN119488946A_ABST
Patent Text Reader

Abstract

The invention relates to the field of molecular sieve catalysts, and discloses a preparation method of a 3D printing molecular sieve catalyst, the prepared 3D printing molecular sieve catalyst and application of the 3D printing molecular sieve catalyst. The molecular sieve with good dispersity and high catalytic activity can be obtained on the aluminosilicate ceramic carrier, the preparation process is simple, a complex three-dimensional structure can be formed without depending on a mold, the prepared molecular sieve catalyst is high in structural precision, the molecular sieve content in the catalyst is high, metal in the catalyst is loaded on the molecular sieve, and the molecular sieve is exposed on the outer surface of the catalyst. The metal sites and the molecular sieve acidic active sites have high accessibility, and the catalytic activity is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of molecular sieve catalysts, and in particular to a method for preparing a 3D printed molecular sieve catalyst and the prepared 3D printed molecular sieve catalyst and its application. Background Art

[0002] In the field of materials science and heterogeneous catalysis, nanometal catalysts have become a research hotspot due to their unique electronic structure, high specific surface area and other physical and chemical properties and excellent catalytic activity, and are widely used in reactions such as small molecule activation and hydrocarbon cracking. However, since the surface energy of metal species increases as their size decreases, metal species dispersed in traditional open structures are thermodynamically unstable and prone to sintering under conditions such as thermal activation, resulting in rapid deactivation, which limits their practical application. In order to improve the stability of metal species, limiting the active metal sites in the pores or cavities of porous materials such as molecular sieves can help control the metal size, increase the dispersion of metal species, and inhibit their migration and agglomeration, thereby improving the thermal stability and catalytic stability of the metal. ZSM-5 belongs to the MFI family of molecular sieves and has straight pores. and sinusoidal pores It is one of the most widely used solid acid catalysts at this stage due to its adjustable acidity, high thermal / hydrothermal stability, and unique shape-selective catalytic effect. At present, a variety of metal ZSM-5 molecular sieves have been reported and applied to catalytic cracking, isomerization, cyclization, aromatization and other reactions (ACS Catalysis 2016, 6, 8321; ACS Catalysis 2023, 13, 1; Energy & Fuels, 2016, 30, 5259). In recent years, with the rising prices of precious metals, the research and development of non-precious metal molecular sieve catalysts has gradually become a hot topic.

[0003] CN201911367038.1 prepared a ZSM-5 molecular sieve containing lanthanum, zinc and / or nickel in the pores by hydrothermal synthesis. The prepared molecular sieve also contains a large number of mesopores, which can increase the diffusion rate of macromolecular reactants or products and improve the carbon capacity of the catalyst. CN202010226208.0 combines molecular sieve synthesis with metal loading in one step, combined with dry gel conversion, to achieve the preparation of molecular sieve-loaded metal catalysts, so that the active metal is evenly dispersed in the molecular sieve micropores. Busca et al. reported a metal-loaded molecular sieve (Fuel Processing Technology 2015, 137, 290–297), which achieved the selective regulation of the ethanol catalytic conversion reaction products by loading non-precious metal Ni species on hydrogen-type ZSM-5 molecular sieves.

[0004] However, the above research systems are all powdered molecular sieve materials. In practical applications, metal-loaded molecular sieve powders need to be processed together with binder / matrix materials into shaped catalysts such as microspheres, granules or strips before they can be used. The structure, composition and catalytic performance of the shaped catalysts will be quite different from those of the initial molecular sieve powders. Therefore, how to optimize the catalyst molding method to improve the accessibility of active sites in metal-loaded molecular sieve catalysts to improve reaction performance is an important issue in the research and development and production of molecular sieve catalysts. In view of this, the development of a shaped catalyst preparation route with easily accessible metal and molecular sieve active sites has important practical significance and application value. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of low accessibility between metal and molecular sieve active center in metal-loaded ZSM-5 molecular sieve catalyst in the prior art, and to provide a preparation method of a 3D printed molecular sieve catalyst and the prepared molecular sieve catalyst and application. The preparation method is simple in process, the metal in the catalyst is loaded on the molecular sieve, and the molecular sieve is exposed to the outer surface of the catalyst, the metal site and the molecular sieve acid active site have high accessibility, and the catalytic activity is high.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a 3D printed molecular sieve catalyst, wherein the method comprises the following steps:

[0007] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;

[0008] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;

[0009] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution;

[0010] (4) hydrothermally crystallizing the aluminosilicate ceramic support in a crystallization incubation solution, and then first calcining the solid product obtained by the hydrothermal crystallization to obtain a sodium-type molecular sieve catalyst;

[0011] (5) exchanging the sodium-type molecular sieve catalyst with ammonium to obtain a hydrogen-type molecular sieve catalyst;

[0012] (6) The hydrogen-type molecular sieve catalyst is impregnated with a metal nickel salt solution, and then the solid product obtained by the impregnation is subjected to a second calcination to obtain a 3D printed molecular sieve catalyst.

[0013] The second aspect of the present invention provides a 3D printed molecular sieve catalyst prepared by the preparation method described in the first aspect.

[0014] Preferably, the 3D printed molecular sieve catalyst comprises 20-55% by mass of ZSM-5 molecular sieve.

[0015] Preferably, the ZSM-5 molecular sieve is distributed on the surface of the 3D printed molecular sieve catalyst and exists in the form of micron particle aggregates. Preferably, the average particle size of the micron particles is 1-5 microns.

[0016] Preferably, in the 3D printed molecular sieve catalyst, the mass percentage of nickel is 0.5-10%, preferably 2-8%.

[0017] Preferably, the micropore volume of the 3D printed molecular sieve catalyst is 0.04-0.1 cm 3 / g; mesopore volume is 0.04-0.09cm 3 / g.

[0018] The third aspect of the present invention provides an application of the 3D printed molecular sieve catalyst prepared by the method described in the first aspect or the 3D printed molecular sieve catalyst described in the second aspect in a catalytic cracking reaction.

[0019] Through the above technical solution, the present invention has the following advantages:

[0020] (1) The preparation method provided by the present invention can establish a model through three-dimensional software, and can customize complex three-dimensional structures suitable for different scenes. It does not rely on high-cost mold making, nor does it require complex post-processing such as cutting and chipping of the carrier. The three-dimensional channel structure of the carrier is simple and controllable;

[0021] (2) The molecular sieve catalyst prepared by the preparation method provided by the present invention has a high molecular sieve content and high structural accuracy, and the molecular sieve is directly exposed to the outer surface of the carrier through in-situ growth, which has the advantage of high accessibility of the active center;

[0022] (3) In the molecular sieve catalyst prepared by the preparation method provided by the present invention, the molecular sieve is in situ grown on the surface of the carrier, and the metal nickel is dispersed in the molecular sieve (microporous aluminosilicate crystals) and is also directly exposed to the outer surface of the carrier, which has the advantage of high accessibility of the metal site; the use of metal nickel has dehydrogenation activity and has the advantage of low cost as a non-precious metal; the molecular sieve catalyst is easy to separate and recover from the synthesis solution, and the synthesis process has low requirements on equipment;

[0023] (4) In the present invention, the prepared molecular sieve catalyst has high catalytic activity in the performance test of hydrocarbon catalytic cracking reaction, has the advantage of reducing bed pressure drop, and has application prospects in the field of catalytic cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a structural diagram of a three-dimensional model established in Example 1;

[0025] Figure 2 is a photo of the 3D printed molecular sieve catalyst prepared in Example 1;

[0026] Figure 3 is the XRD pattern of the 3D printed molecular sieve catalyst prepared in Example 1;

[0027] Figure 4 is a scanning electron microscope image of the 3D printed molecular sieve catalyst prepared in Example 1;

[0028] Figure 5 is a transmission electron microscopy image of the 3D printed molecular sieve catalyst prepared in Example 1;

[0029] Figure 6 is the EDS-Mapping element distribution diagram of the 3D printed molecular sieve catalyst prepared in Example 1;

[0030] Figure 7 is the isothermal adsorption curve of the 3D printed molecular sieve catalyst prepared in Example 1;

[0031] Figure 8 This is the pore distribution curve of the 3D printed molecular sieve catalyst prepared in Example 1. DETAILED DESCRIPTION

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] A first aspect of the present invention provides a method for preparing a 3D printed molecular sieve catalyst, the method comprising the following steps:

[0034] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;

[0035] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;

[0036] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution;

[0037] (4) hydrothermally crystallizing the aluminosilicate ceramic support in a crystallization incubation solution, and then first calcining the solid product obtained by the hydrothermal crystallization to obtain a sodium-type molecular sieve catalyst;

[0038] (5) exchanging the sodium-type molecular sieve catalyst with ammonium to obtain a hydrogen-type molecular sieve catalyst;

[0039] (6) The hydrogen-type molecular sieve catalyst is impregnated with a metal nickel salt solution, and then the solid product obtained by the impregnation is subjected to a second calcination to obtain a 3D printed molecular sieve catalyst.

[0040] In the present invention, the aluminosilicate ceramic carrier is hydrothermally crystallized in a crystallization incubation solution, and a molecular sieve with good dispersibility and high catalytic activity can be obtained on the aluminosilicate ceramic carrier. The preparation process is simple and can form a complex three-dimensional structure without relying on a mold. The prepared molecular sieve catalyst has high structural accuracy, high molecular sieve content in the catalyst, and high catalytic activity.

[0041] In the present invention, preferably, the aluminosilicate photosensitive resin slurry in step (1) can be obtained by mixing aluminosilicate and photosensitive resin. There is no particular limitation on the mixing method. According to a preferred embodiment of the present invention, the mixing can be achieved by ball milling, the ball milling speed is 250-500 rpm, preferably 280-450 rpm, and the ball milling time is 3-18 hours, preferably 5-15 hours.

[0042] According to the present invention, preferably, the aluminosilicate comprises silicon-based powder and auxiliary powder, the mass percentage of silicon-based powder on a dry basis is 35-65%, preferably 45-60%, and the mass percentage of auxiliary powder on a dry basis is 35-65%, preferably 40-55%. The use of such aluminosilicate with such a preferred composition is more conducive to the carrier material obtained after sintering taking into account both structural stability and chemical activity under hydrothermal conditions.

[0043] In the present invention, the aluminosilicate has the conventional meaning in the art. Aluminosilicate is a class of substances including commonly used mineral soils, the main components of which are aluminum oxide and silicon dioxide. The molecular formula can be expressed as xAl2O3·ySiO2, wherein the ratio of aluminum oxide to silicon dioxide is not constant.

[0044] In the present invention, there is no particular limitation on the particle size of the aluminosilicate, which can be larger particles or smaller powders, as long as the aluminosilicate is evenly distributed in the carrier. If larger particles are used, it is preferred to further improve their uniformity through subsequent ball milling. Preferably, the particle size D90 of the aluminosilicate is in the range of 0.5-100 μm.

[0045] In the present invention, preferably, the above silicon-based powder is mixed with an auxiliary powder to obtain aluminosilicate, and the silicon-based powder can be used as a silicon source for growing molecular sieves on a carrier in a subsequent preparation process. When the amount of the silicon-based powder added is too much, the silicon dissolution degree of the carrier after sintering is too high during the hydrothermal crystallization process, and the in-situ molecular sieve growth reaction rate on the carrier surface is too high, making the carrier structure unstable and collapsing, and no longer maintaining the original self-supporting structure. When the amount of silicon-based powder added is insufficient, the silicon dissolution of the carrier after sintering is limited during the hydrothermal crystallization process, resulting in a too low in-situ molecular sieve growth reaction rate on the carrier surface, so that the molecular sieve content in the catalyst finally obtained is low, and the catalytic reaction requirements cannot be met.

[0046] In the present invention, there is no particular limitation on the particle sizes of the silicon-based powder and the auxiliary powder. It is preferred that the particle size of the aluminosilicate obtained after mixing meets the above-mentioned particle size requirements.

[0047] According to the present invention, the silicon-based powder may be conventional silicon-based powder in the art, and those skilled in the art can make an adaptive selection according to needs. Preferably, the silicon-based powder is selected from at least one of silicon dioxide, white carbon black and diatomaceous earth.

[0048] According to the present invention, there is no particular limitation on the auxiliary powder, as long as it is chemically inert under hydrothermal conditions to maintain the stability of the self-supporting structure. Preferably, the auxiliary powder is selected from at least one of kaolin, metakaolin, bentonite and montmorillonite.

[0049] According to the present invention, the amount of the aluminosilicate and the photosensitive resin can be selected in a relatively wide range, so as to ensure that the 3D printing process proceeds smoothly. Preferably, the mass ratio of the aluminosilicate to the photosensitive resin is 0.5-1:1, such as 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, and any range between any two values, preferably 0.6-0.9:1.

[0050] According to the present invention, the specific composition of the photosensitive resin has a wide range of selections and can be selected according to conventional technical means in the art. Preferably, the raw materials of the photosensitive resin include 1-5% of photoinitiator, 30-65% of prepolymer, and 30-65% of monomer by mass percentage, preferably including 1.5-4% of photoinitiator, 35-60% of prepolymer, and 37-62% of monomer by mass percentage. The photosensitive resin composed of the above raw materials is used for 3D printing, which has fast curing speed and high production efficiency.

[0051] In the present invention, the photoinitiator can be a conventional photoinitiator in the art. Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and isopropylthioxanthone (ITX).

[0052] In the present invention, the prepolymer may be a conventional acrylate prepolymer in the art. Preferably, the prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer.

[0053] In the present invention, the monomer may be a conventional monomer in the art. Preferably, the monomer is selected from at least one of 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA) and trimethylolpropane triacrylate (TMPTA).

[0054] In the present invention, a 3D printing method is used to prepare an aluminosilicate ceramic body, a modeling software is used to perform a three-dimensional structure design, and an aluminosilicate photosensitive resin slurry is poured into a DLP light-curing printer material cylinder for printing to obtain an aluminosilicate ceramic body. In the present invention, "aluminosilicate ceramic body" is a general term for the prepared bodies, and the printing method can be used to customize complex three-dimensional structures suitable for different scenes, without relying on molds, and does not require complex post-processing of the carrier, and the three-dimensional channel structure of the carrier is simple and controllable.

[0055] In the present invention, preferably, a modeling software is used for three-dimensional structure design, and the modeling software is selected from SolidWorks, 3DMAX, AutoCAD or Materialise Magics.

[0056] According to the present invention, preferably, the conditions for 3D printing include: the light curing exposure power is 0.5-5mW / cm 2 The exposure time of the first layer is 15-30s, the exposure time of other layers is 5-15s, and the thickness of a single layer of photocuring is 20-100μm.

[0057] In the present invention, preferably, the obtained aluminosilicate ceramic body is also cleaned after printing. There is no particular limitation on the cleaning conditions, and those skilled in the art can make appropriate selections. According to a preferred embodiment of the present invention, anhydrous ethanol is used for sufficient cleaning.

[0058] The present invention does not particularly limit the size and structural shape of the aluminosilicate ceramic body, and those skilled in the art can make appropriate selections according to the specific application scenarios of the prepared catalyst. The present invention subsequently provides a specific preferred embodiment for use in a catalytic cracking catalyst, but the present invention is not limited thereto.

[0059] According to the present invention, preferably, the cross-section of the aluminosilicate ceramic body is 0.5-15 cm. In the present invention, the cross-section of the aluminosilicate ceramic body is a cross-section parallel to the bottom surface, and the cross-section size is the straight-line distance obtained by connecting the two farthest end points in the cross-section.

[0060] In the present invention, the aluminosilicate ceramic body provides a skeleton for the molecular sieve catalyst. The body has a multi-porous structure and forms an aluminosilicate ceramic carrier after sintering, so that the molecular sieve seeds in the crystallization incubation solution can grow rapidly on the carrier, thereby increasing the mass percentage of the molecular sieve (preferably ZSM-5) in the prepared molecular sieve catalyst.

[0061] According to the present invention, preferably, the aluminosilicate ceramic carrier has a multi-porous self-supporting three-dimensional structure. The present invention has no special limitation on the multi-porous self-supporting three-dimensional structure, which has the conventional interpretation in the art. Specifically, the "self-supporting" means that the aluminosilicate ceramic carrier has its own strength and rigidity, and can maintain its shape and stability without external support. The "multi-porous" means that the main frame of the aluminosilicate ceramic carrier has a multi-porous structure. There is no special limitation on the distribution of the pores, and it can be appropriately selected according to the specific catalyst application scenario. The distribution of the pores can be uniform, symmetrical, or uneven and asymmetrical. In order to further improve the application effect of the catalyst in catalytic cracking reactions, it is further preferred that the aluminosilicate ceramic carrier is a self-supporting three-dimensional structure with parallel radial and axial interconnected pore structures. The specific pore structure is as follows Figure 1 and Figure 2 shown.

[0062] The present invention has no special limitation on the interconnected channel structure, which has the conventional meaning in the art. In the present invention, the interconnected channel structure refers to the vertical and horizontal channels of the aluminosilicate ceramic carrier being cross-connected and having good permeability.

[0063] According to the present invention, preferably, the sintering conditions in step (2) include: a temperature of 1100-1300° C. and a time of 5-20 hours. Further preferably, the sintering conditions in step (2) include: a temperature of 1150-1250° C. and a time of 8-16 hours.

[0064] In the present invention, the aluminosilicate ceramic body is sintered in step (2), and those skilled in the art can adjust the heating rate of the sintering process as needed. Preferably, the heating rate is 0.1-10°C / min, preferably 0.5-5°C / min.

[0065] According to the present invention, preferably, the method also includes pyrolyzing the aluminosilicate ceramic body before sintering to remove organic matter in the body, and the pyrolysis conditions include: temperature of 350-550°C and time of 5-15h; preferably, the pyrolysis conditions include: temperature of 380-520°C and time of 6-13h.

[0066] In the present invention, those skilled in the art can adjust the heating rate of the pyrolysis process as needed. Preferably, the heating rate of the pyrolysis process is 0.1-5°C / min, preferably 0.5-2°C / min.

[0067] According to the present invention, preferably, in the crystallization mother solution, the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, the alkali source is calculated as Na2O, and the molar ratio of SiO2:Al2O3:template:Na2O:H2O is 1:(0.003-0.03):(0.05-0.25):(0.05-0.3):(30-55), preferably 1:(0.005-0.025):(0.08-0.2):(0.08-0.25):(35-50).

[0068] According to the present invention, the silicon source may be a conventional silicon source in the art, and those skilled in the art may make an adaptive selection according to needs, preferably silica sol and / or tetraethyl orthosilicate.

[0069] According to the present invention, the aluminum source may be a conventional aluminum source in the art, and those skilled in the art may make an adaptive selection as needed, preferably selected from at least one of aluminum sulfate, aluminum isopropoxide and aluminum trichloride.

[0070] In the present invention, preferably, the alkali source may be a conventional alkali source in the art, and those skilled in the art may make an adaptive selection according to needs, preferably sodium hydroxide.

[0071] In the present invention, the template agent has a wide selection range and can be adaptively selected according to the specific type of molecular sieve to be synthesized. Preferably, the template agent is an organic amine microporous template agent known to those skilled in the art that can be used to prepare ZSM-5, preferably tetrapropylammonium hydroxide and / or tetrapropylammonium bromide.

[0072] In the present invention, preferably, the silicon source, aluminum source and template are used to provide molecular sieve seeds for the crystallization mother solution, which helps to accelerate the growth rate of the molecular sieve on the aluminosilicate ceramic carrier and shorten the crystallization time of the molecular sieve.

[0073] According to the present invention, preferably, the crystallization conditions in step (3) include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 3-10 h, preferably 4-9 h.

[0074] In the present invention, the reaction equipment for the crystallization and hydrothermal crystallization has a wide range of options, and those skilled in the art can make adaptive choices as needed, preferably in a crystallization kettle. In the present invention, it is preferred that after the crystallization and / or hydrothermal crystallization is completed, the crystallization kettle is cooled (preferably to room temperature) and then opened. This preferred embodiment avoids the safety hazard when the kettle is opened due to the self-generated pressure in the kettle caused by the crystallization reaction at high temperature.

[0075] In the present invention, preferably, the crystallization mother liquor is crystallized under the above conditions to obtain a crystallization incubation solution, which can further improve the crystallinity of the prepared molecular sieve catalyst. The crystallization incubation solution contains molecular sieve seeds. From the perspective of crystal growth kinetics, the use of the incubation solution can significantly shorten the crystal nucleation period (nucleation period) on the carrier surface, thereby accelerating the molecular sieve crystallization process on the carrier surface.

[0076] According to the present invention, preferably, in step (4), the mass ratio of the aluminosilicate ceramic carrier to the crystallization incubation solution is 1:6-20, such as 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, and any range between any two values, preferably 1:8-15. This preferred embodiment is more conducive to matching the dissolution rate of the silicon species of the carrier itself and the crystallization rate of the surface molecular sieve, and obtaining a crystallized product that takes into account both crystallinity and self-supporting structural strength.

[0077] According to the present invention, preferably, the conditions for the hydrothermal crystallization include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 12-40 h, preferably 15-35 h.

[0078] In the present invention, preferably, the method further comprises: post-processing the solid product obtained by hydrothermal crystallization, wherein the post-processing comprises washing and drying. The washing may be performed by conventional methods and conditions in the art, and according to some preferred embodiments of the present invention, the washing may be performed by deionized water.

[0079] In the present invention, drying can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, drying can be carried out in an oven under the conditions of: drying at 60-120° C. for 2-10 hours.

[0080] According to the present invention, there is no particular limitation on the conditions of the first calcination, as long as the template in the solid product can be removed. Preferably, the conditions of the first calcination include: a temperature of 500-600°C and a time of 4-8 hours. There is no particular limitation on the calcination equipment. Preferably, the calcination can be performed in a muffle furnace.

[0081] In the present invention, the "first roasting", "second roasting" and "third roasting" do not limit the order of execution, but are only used to distinguish different roasting processes. The roasting conditions and roasting equipment used may be the same or different.

[0082] According to the present invention, the process of ammonium exchange is not particularly limited, and is a conventional ammonium exchange operation in the art. According to a preferred embodiment of the present invention, the sodium molecular sieve catalyst is placed in an ammonium salt solution. Preferably, in step (5), the conditions of the ammonium exchange include: a temperature of 60-90°C, preferably 70-80°C, and a time of 0.5-3h, preferably 1-2h.

[0083] According to the present invention, preferably, the number of ammonium exchanges is 2-4 times.

[0084] According to the present invention, preferably, the mass ratio of the sodium molecular sieve catalyst to the ammonium salt solution is 1:8-20, such as 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, and any range between any two values, preferably 1:10-15. This preferred embodiment is more conducive to replacing the sodium ions in the sodium molecular sieve catalyst with ammonium ions to obtain a hydrogen molecular sieve catalyst.

[0085] In the present invention, the ammonium salt is an inorganic ammonium salt known to those skilled in the art and can be used to prepare hydrogen-type molecular sieve catalysts, preferably ammonium chloride and / or ammonium sulfate.

[0086] According to the present invention, preferably, the mass fraction of the ammonium salt in the ammonium salt solution is 5-30%, preferably 10-20%.

[0087] In the present invention, preferably, step (5) further comprises: post-treating the solid product obtained by ammonium exchange, wherein the post-treating comprises washing, drying and a third roasting. The washing may be carried out by conventional methods and conditions in the art, and according to some preferred embodiments of the present invention, the washing may be carried out by deionized water.

[0088] In the present invention, drying can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, drying can be carried out in an oven under the conditions of: drying at 60-120° C. for 2-10 hours.

[0089] In the present invention, preferably, the conditions of the third roasting are not particularly limited, as long as the nitrogen element in the ammonium ions in the solid product can be removed in the form of ammonia. Preferably, the conditions of the third roasting include: a temperature of 500-600°C and a time of 1-4h. The roasting equipment is not particularly limited. Preferably, the third roasting can be performed in a muffle furnace.

[0090] According to the present invention, preferably, in step (6), the impregnation conditions include: temperature of 20-30°C, time of 1-5 hours, and vacuum degree of -0.05 to -0.1 MPa. In the present invention, vacuum impregnation helps to replace hydrogen ions with nickel ions.

[0091] According to the present invention, preferably, the amount of the hydrogen-type molecular sieve catalyst and the metal nickel salt solution is such that the mass percentage of nickel in the prepared 3D printed molecular sieve catalyst is 0.5-10%, preferably 2-8%. The mass ratio of the hydrogen-type molecular sieve catalyst carrier to the metal nickel salt solution is 1:0.06-1.29, such as 1:0.06, 1:0.12, 1:0.25, 1:0.38, 1:0.51, 1:0.64, 1:0.77, 1:0.89, 1:1.02, 1:1.15, 1:1.28, 1:1.29, and any range composed of any two values, preferably 1:0.25-1.02. The use of this preferred embodiment is more conducive to replacing the hydrogen ions in the hydrogen-type molecular sieve catalyst with nickel ions to obtain a 3D printed molecular sieve catalyst loaded with metal nickel.

[0092] According to the present invention, preferably, the metal nickel salt is an organic nickel salt and / or an inorganic nickel salt, preferably at least one selected from nickel nitrate, nickel chloride and nickel acetate.

[0093] According to the present invention, preferably, the mass fraction of the metal nickel salt in the metal nickel salt solution is 5-20%, preferably 10-15%.

[0094] In the present invention, the impregnation may be carried out using conventional impregnation equipment in the art. According to some preferred embodiments of the present invention, the impregnation may be carried out in a rotary evaporator and / or a schlenk tube.

[0095] The present invention further includes drying the solid product after impregnation. The drying can be carried out by conventional methods and conditions in the art. According to some preferred embodiments of the present invention, the drying can be carried out in an oven at 60-120° C. for 2-10 hours.

[0096] In the present invention, there is no particular limitation on the conditions of the second calcination, as long as the nickel ions in the solid product can form stable +2-valent or +3-valent nickel ions. Preferably, the conditions of the second calcination include: a temperature of 400-600°C and a time of 1-4h. There is no particular limitation on the calcination equipment. Preferably, the second calcination can be performed in a muffle furnace.

[0097] According to the present invention, preferably, in the 3D printed molecular sieve catalyst prepared by the method, the mass percentage of ZSM-5 molecular sieve is 20-55%, preferably 35-52%.

[0098] In the present invention, the mass percentage of the molecular sieve in the molecular sieve catalyst is expressed by relative crystallinity, and with reference to ASTM D3906-03 standard, commercial ZSM-5 molecular sieve is used as the standard (Tianjin Nanhua Catalyst Co., Ltd., Na-type ZSM-5 molecular sieve of Nankai University Catalyst Factory, silicon-aluminum ratio 25), and the commercial ZSM-5 crystallinity is defined as 100%. The ratio of the characteristic peak area of ​​the 2θ angle between 22.0-25.0° and the characteristic peak area of ​​the standard molecular sieve in the XRD spectrum of the crystallized product is defined as relative crystallinity. Test instrument: D5005 X-ray diffractometer of Siemens, Germany. Test conditions: Cu target, Kα radiation, solid detector, tube voltage 40kV, tube current 40mA, step scan, step width 0.02°, prefabrication time 2s, scanning range 5°-70°.

[0099] The second aspect of the present invention provides a 3D printed molecular sieve catalyst prepared by the preparation method described in the first aspect.

[0100] According to the present invention, preferably, the 3D printed molecular sieve catalyst comprises 20-55% by mass of ZSM-5 molecular sieve, and further preferably, the 3D printed molecular sieve catalyst comprises 35-52% by mass of ZSM-5 molecular sieve.

[0101] According to the present invention, preferably, the 3D printed molecular sieve catalyst comprises 0.5-10% by mass of nickel, and further preferably, the 3D printed molecular sieve catalyst comprises 2-8% by mass of nickel.

[0102] In the present invention, the mass percentage of nickel in the 3D printed molecular sieve catalyst is obtained by testing with an inductively coupled plasma spectrometer (5110ICP, Agilent Technologies).

[0103] According to the present invention, preferably, the ZSM-5 molecular sieve is distributed on the surface of the nickel-loaded 3D printed molecular sieve catalyst and exists in the form of micron particle aggregates. Preferably, the average particle size of the micron particles is 1-5 microns, and more preferably 1.5-4 microns.

[0104] In the present invention, the average particle size of the ZSM-5 molecular sieve micron particles of the 3D printed molecular sieve catalyst is tested in a scanning electron microscope (Hitachi scanning electron microscope, S-4800), and the average value of 20 molecular sieve grain sizes is randomly measured by Nano Measurer software. In the measurement process, the size of a molecular sieve grain is the straight-line distance obtained by connecting the two farthest endpoints on the particle in the electron microscopic image.

[0105] In the present invention, preferably, the metallic nickel is distributed on the outer surface and pore openings of the ZSM-5 molecular sieve and exists in the form of nanoparticles, and the average particle size of the metallic nickel particles is 10-100 nanometers, for example, 10 nanometers, 15 nanometers, 20 nanometers, 30 nanometers, 40 nanometers, 50 nanometers, 60 nanometers, 70 nanometers, 80 nanometers, 90 nanometers, 100 nanometers, and any range between any two values, more preferably 15-50 nanometers.

[0106] In the present invention, the average particle size of the metal nickel particles in the 3D printed molecular sieve catalyst is tested in a transmission electron microscope (Hitachi transmission electron microscope, HT-7800), and the average value of 20 metal nickel particle sizes is randomly measured by NanoMeasurer software. In the measurement process, the size of a metal nickel particle is the straight-line distance obtained by connecting the two farthest end points on the particle in the electron microscopic image.

[0107] According to the present invention, preferably, the micropore volume of the catalyst is 0.04-0.1 cm 3 / g, preferably 0.05-0.09cm 3 / g; mesopore volume is 0.04-0.09cm 3 / g, preferably 0.05-0.08cm 3 / g.

[0108] In the present invention, the micropore volume and mesopore volume of the molecular sieve catalyst are measured by low temperature nitrogen adsorption capacity method, and the test instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics. Test conditions: the sample is vacuum degassed for 4 hours at 1.33Pa and 300°C, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, adsorption and desorption isotherms are measured, and the micropore volume and mesopore volume are calculated using the BET formula.

[0109] In the present invention, the prepared 3D printed molecular sieve catalyst has a high molecular sieve content and high structural accuracy, and the ZSM-5 molecular sieve is directly exposed to the outer surface of the carrier through in-situ growth, which has the advantage of high accessibility of the active center.

[0110] In the present invention, transmission electron microscopy was used to observe that the metallic nickel in the prepared 3D printed molecular sieve catalyst was mainly located at the pore openings of the molecular sieve (microporous aluminosilicate crystals) and was also directly exposed to the outer surface of the molecular sieve, which has the advantage of high accessibility of metal sites.

[0111] The third aspect of the present invention provides an application of the 3D printed molecular sieve catalyst prepared by the method described in the first aspect or the 3D printed molecular sieve catalyst described in the second aspect in a catalytic cracking reaction.

[0112] In the present invention, preferably, the reaction conditions of the catalytic cracking reaction are: reaction pressure of 0.09-0.3 MPa, reaction temperature of 450-600°C, raw material feed weight space velocity of 20-100h -1 .

[0113] In the present invention, there is no particular limitation on the reaction device for the catalytic cracking reaction, and those skilled in the art can make an appropriate selection according to the application scenario of the molecular sieve catalyst. According to a preferred embodiment of the present invention, the catalytic cracking reaction can be carried out in a fixed bed reactor.

[0114] In the present invention, the prepared molecular sieve catalyst has high catalytic activity and has the advantage of reducing bed pressure drop, and can be widely used in catalytic cracking reactions.

[0115] According to a particularly preferred embodiment of the present invention, a method for preparing a 3D printed molecular sieve catalyst comprises the following steps:

[0116] (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body;

[0117] (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier;

[0118] (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution;

[0119] (4) hydrothermally crystallizing the aluminosilicate ceramic support in a crystallization incubation solution, and then first calcining the solid product obtained by the hydrothermal crystallization to obtain a sodium-type molecular sieve catalyst;

[0120] (5) exchanging the sodium-type molecular sieve catalyst with ammonium to obtain a hydrogen-type molecular sieve catalyst;

[0121] (6) impregnating the hydrogen-type molecular sieve catalyst with a metal nickel salt solution, and then performing a second calcination on the solid product obtained by the impregnation to obtain a 3D printed molecular sieve catalyst;

[0122] In the crystallization mother solution, the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as Na2O, and the molar ratio of SiO2:Al2O3:template:Na2O:H2O is 1:(0.005-0.025):(0.08-0.2):(0.08-0.25):(35-50);

[0123] The crystallization temperature is 165-180°C and the crystallization time is 4-9h;

[0124] The amount of the hydrogen-type molecular sieve catalyst and the metal nickel salt solution is such that the mass percentage of nickel in the prepared 3D printing molecular sieve catalyst is 2-8%.

[0125] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, the reagents and materials used can be obtained commercially, and the room temperature is 25°C;

[0126] The ball milling was carried out using a Juchuang environmental protection vertical planetary ball mill (model JC-QM-0.4);

[0127] The three-dimensional model is established by Solidworks software;

[0128] The 3D printing is completed by a sinking DLP-3D printer (model SU136A or SU-100A) of Foshan Guanglei Intelligent Manufacturing Co., Ltd. (light source wavelength: 405nm);

[0129] The test methods and conditions for the mass percentage content, surface morphology, average particle size and pore structure of the molecular sieve catalyst and the mass percentage content and particle size of nickel are described in the aforementioned specification and will not be repeated here.

[0130] Example 1

[0131] (1) Preparation of aluminosilicate ceramic green body:

[0132] (1-1) Using diatomite as a silicon-based powder and metakaolin as an auxiliary powder, the silicon-based powder mass fraction is 60% (on a dry basis) and the auxiliary powder mass fraction is 40% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 8 μm;

[0133] (1-2) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) is used as a photoinitiator, polyurethane acrylate prepolymer is used as a prepolymer, and 1,6-hexanediol diacrylate (HDDA) is used as a monomer, and the mixture is mixed according to the ratio of 4% of the photoinitiator, 35% of the prepolymer, and 61% of the monomer to obtain a photosensitive resin;

[0134] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.65:1, and fully ball milling in a ball mill for 14 hours (rotation speed 280 rpm) to obtain aluminosilicate photosensitive resin slurry;

[0135] (1-4) Perform three-dimensional structure design, import the three-dimensional model file into the 3D printing equipment, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning. The cross-sectional diameter of the aluminosilicate ceramic body is 1.5cm, the height is 1.43cm, and the interval between different strips on the same horizontal plane is 0.08cm.

[0136] (2) The formed aluminosilicate ceramic body is dried, pyrolyzed and sintered. The specific pyrolysis and sintering conditions are: heating from room temperature to 450°C at a heating rate of 0.5°C / min and maintaining for 8 hours; heating from 450°C to 1200°C at a heating rate of 3°C / min and maintaining for 15 hours to obtain an aluminosilicate ceramic carrier.

[0137] (3) Using silica sol (40wt% SiO2, Qingdao Junqiang New Materials Co., Ltd.) and aluminum sulfate (99wt%, Innochem) as the silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) as the template, the silicon source, aluminum source, template and sodium hydroxide are added into water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:Na2O:H2O, is 1:0.025:0.1:0.25:35. The above mixture is crystallized at 165°C for 9 hours to obtain a crystallization incubation solution.

[0138] (4) placing the aluminosilicate ceramic carrier in a crystallization incubation solution, wherein the carrier:crystallization incubation solution mass ratio is 1:13, and hydrothermally crystallizing the carrier-incubation solution mixture at 170°C for 30 hours. After the hydrothermal crystallization is completed, the hydrothermal crystallization product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 5 hours to obtain a sodium-type molecular sieve catalyst.

[0139] (5) The sodium molecular sieve catalyst is placed in an ammonium salt solution for ammonium exchange, the mass ratio of the sodium molecular sieve catalyst to the ammonium salt solution is 1:10, the ammonium salt is ammonium chloride, the mass fraction of ammonium chloride in the ammonium salt solution is 10%, the ammonium exchange temperature is 80°C, the reaction time is 1h, and the exchange is repeated 3 times. After the ammonium exchange is completed, the obtained solid product is dried at 100°C for 4 hours and calcined at 550°C for 2 hours to obtain a hydrogen molecular sieve catalyst.

[0140] (6) The hydrogen-type molecular sieve catalyst is impregnated in a metal nickel salt solution, wherein the mass ratio of the hydrogen-type molecular sieve catalyst to the metal nickel salt solution is 1:0.64; the metal nickel salt is nickel acetate, and the mass fraction of the metal nickel salt in the metal nickel salt solution is 10%. The impregnation conditions are: in a Schlenk tube, vacuum impregnation for 3 hours at 25°C, and the vacuum degree is -0.1MPa. Then, the solid product obtained after impregnation is dried at 100°C for 5 hours, and then calcined at 550°C for 3 hours to obtain a 3D printed molecular sieve catalyst.

[0141] Figure 1 This is the three-dimensional model structure diagram established in Example 1. The three-dimensional structure design is performed through modeling software, and the structural shape of the molecular sieve catalyst can be selected according to actual needs. Figure 2 This is a photo of the 3D printed molecular sieve catalyst prepared in Example 1. The molecular sieve catalyst obtained by 3D printing realizes high-precision, digital design of the molecular sieve catalyst and has better regularity.

[0142] The XRD spectrum of the catalyst prepared in Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the synthesized 3D printed molecular sieve catalyst has the characteristic diffraction peaks of ZSM-5 molecular sieve, and an obvious five-finger diffraction peak appears at 22.0-25.0° at 2θ. The surface nickel dispersion is good, and no diffraction peaks of nickel oxide or nickel trioxide are observed. Figure 4 , Figure 5 They are scanning electron microscope images and transmission electron microscope images of the catalyst of Example 1, Figure 4 It can be seen that the outer surface of the catalyst is densely distributed with ZSM-5 molecular sieve particles, which mainly exist in the form of micron particle aggregates with an average particle size of 1.8 microns. The ZSM-5 molecular sieve is directly exposed to the outer surface of the carrier through in-situ growth, which has the advantage of high accessibility of the active center. Figure 5 The presence of nickel metal species on the surface can be observed in the transmission electron microscopy image. Figure 5 The part marked by the middle circle is the nickel metal on the surface of the molecular sieve. Figure 6 EDS-Mapping element distribution map of 3D printed molecular sieve catalyst. Figure 6The bright spots in the right half are the distribution of nickel metal on the surface of the molecular sieve, which shows that the surface nickel metal species are well dispersed.

[0143] Figure 7 is the isothermal adsorption curve of the 3D printed molecular sieve catalyst prepared in Example 1, Figure 8 is the pore distribution curve of the 3D printed molecular sieve catalyst prepared in Example 1, such as Figure 7 , Figure 8 As shown, a hysteresis loop can be observed in the adsorption isotherm of the 3D printed molecular sieve catalyst, and the presence of mesopores in the sample can be observed from the pore size distribution curve.

[0144] Comparative Example 1

[0145] The 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that in step (1), no silicon-based powder was used, and all auxiliary powders (kaolin) were used to prepare aluminosilicate to prepare the 3D printed molecular sieve catalyst sample.

[0146] Comparative Example 2

[0147] The 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that in step (6), the same mass of ferric chloride was used instead of nickel chloride to prepare an iron-loaded 3D printed molecular sieve catalyst sample.

[0148] Comparative Example 3

[0149] The hydrogen-type ZSM-5 powder loaded with nickel metal (Tianjin Nanhua Catalyst Co., Ltd., Na-type ZSM-5 molecular sieve of Nankai University Catalyst Factory, silicon-aluminum ratio 25) was tableted to prepare 40-60 mesh molecular sieve particles, which were directly used for the evaluation of alkane molecular catalytic cracking. Except for the different catalysts, the other reaction evaluation conditions were the same as in Example 1, recorded as pure molecular sieve-nickel catalyst.

[0150] Comparative Example 4

[0151] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that nickel acetate was directly added to the crystallization mother solution in step (3) and step (6) was not performed, thereby preparing a 3D printed molecular sieve catalyst sample.

[0152] Example 2

[0153] (1) Preparation of aluminosilicate ceramic green body:

[0154] (1-1) Using white carbon as a silicon-based powder and bentonite as an auxiliary powder, the mass fraction of the silicon-based powder is 40% (on a dry basis) and the mass fraction of the auxiliary powder is 60% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 23.7 μm;

[0155] (1-2) using isopropylthioxanthone (ITX) as a photoinitiator, using polyurethane acrylate prepolymer as a prepolymer, and using trimethylolpropane triacrylate (TMPTA) as a monomer, the mixture is mixed according to the ratio of 1.5% of the photoinitiator, 60% of the prepolymer, and 38.5% of the monomer to obtain a photosensitive resin;

[0156] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.85:1, and fully ball milling in a ball mill for 8 h (rotation speed 400 rpm) to obtain aluminosilicate photosensitive resin slurry;

[0157] (1-4) Perform 3D structure design, import the 3D model file into the 3D printing device, perform 3D printing according to the 3D model of Example 1, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning.

[0158] (2) The formed aluminosilicate ceramic body is dried, pyrolyzed and sintered. The specific conditions are: heating from room temperature to 500°C at a heating rate of 0.5°C / min and maintaining for 6 hours; heating from 500°C to 1200°C at a heating rate of 3°C / min and maintaining for 10 hours to obtain an aluminosilicate ceramic carrier.

[0159] (3) Silica sol (40wt% SiO2, Qingdao Junqiang New Materials Co., Ltd.) and aluminum sulfate (99wt%, Innochem) were used as silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) was used as template. The silicon source, aluminum source, template and sodium hydroxide were added to water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:Na2O:H2O, was 1:0.005:0.15:0.1:45. The above mixture was crystallized at 180°C for 4.5 hours to obtain a crystallization incubation solution.

[0160] (4) The aluminosilicate ceramic carrier is placed in a crystallization incubation solution, wherein the mass ratio of the carrier to the crystallization incubation solution is 1:6, and the mixture of the carrier and the crystallization incubation solution is hydrothermally crystallized at 180°C for 15 hours. After the crystallization is completed, the crystallized product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 5 hours to obtain a 3D printed molecular sieve catalyst sample.

[0161] (5) placing the sodium molecular sieve catalyst in an ammonium salt solution for ammonium exchange. The mass ratio of the sodium molecular sieve catalyst carrier to the ammonium salt solution is 1:10, the ammonium salt is ammonium chloride, the mass fraction of ammonium chloride in the ammonium salt solution is 10%, the ammonium exchange temperature is 80°C, the reaction time is 1h, and the exchange is repeated 3 times. After the ammonium exchange is completed, the solid product obtained after the ammonium exchange is dried at 100°C for 4 hours and calcined at 550°C for 2 hours to obtain a hydrogen molecular sieve catalyst.

[0162] (6) The hydrogen-type molecular sieve catalyst is impregnated in a metal nickel salt solution, wherein the mass ratio of the hydrogen-type molecular sieve catalyst carrier to the metal nickel salt solution is 1:0.77, the metal nickel salt is nickel acetate, and the mass fraction of the metal nickel salt solution is 13.5%. The impregnation conditions include: impregnation in a rotary evaporator, and the impregnation conditions are: vacuum impregnation at 25°C for 5 hours, and the vacuum degree is -0.09MPa. Then, the solid product obtained after the impregnation is dried and calcined, and the drying conditions include: temperature of 110°C and time of 4 hours, and the calcination conditions include: temperature of 600°C and time of 2h.

[0163] Example 3

[0164] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that the mass fraction of the metal nickel salt in step (6) was 5%, and a 3D printed molecular sieve catalyst sample was prepared.

[0165] Example 4

[0166] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that the mass ratio of the hydrogen-type molecular sieve catalyst to the metal nickel salt solution in step (6) was 1:1.28, and a 3D printed molecular sieve catalyst sample was prepared.

[0167] Example 5

[0168] The 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that the hydrogen-type molecular sieve catalyst was not impregnated under normal temperature and negative pressure conditions, but the metal nickel salt solution was directly heated and evaporated to prepare the 3D printed molecular sieve catalyst sample.

[0169] Example 6

[0170] A 3D printed molecular sieve catalyst was prepared according to the method of Example 1, except that the metal nickel salt in step (6) was changed to nickel sulfate with an equal mass fraction to obtain a 3D printed molecular sieve catalyst.

[0171] Example 7

[0172] (1) Preparation of aluminosilicate ceramic green body:

[0173] (1-1) using silicon dioxide as a silicon-based powder and kaolin as an auxiliary powder, the silicon-based powder is mixed at a mass fraction of 50% (on a dry basis) and the auxiliary powder is mixed at a mass fraction of 50% (on a dry basis) to obtain aluminosilicate, wherein the D90 particle size of the aluminosilicate is 12.5 μm;

[0174] (1-2) using phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (819) as a photoinitiator, using polyurethane acrylate prepolymer as a prepolymer, and using tripropylene glycol diacrylate (TPGDA) as a monomer, the mixture is mixed at a ratio of 3% of the photoinitiator, 45% of the prepolymer, and 52% of the monomer to obtain a photosensitive resin;

[0175] (1-3) mixing aluminosilicate and photosensitive resin in a mass ratio of 0.72:1, and fully ball milling in a ball mill for 10 h (rotation speed 350 rpm) to obtain aluminosilicate photosensitive resin slurry;

[0176] (1-4) Perform 3D structure design, import the 3D model file into the 3D printing device, perform 3D printing according to the 3D model of Example 1, pour the aluminosilicate photosensitive resin slurry into the DLP light-curing printer material tank for printing, and the printing parameters are: exposure power 1mW / cm 2 , exposure time 10s (first layer exposure time 20s); after printing, the obtained aluminosilicate ceramic body is placed in anhydrous ethanol for thorough cleaning.

[0177] (2) The formed aluminosilicate ceramic body is dried, pyrolyzed and sintered. The specific pyrolysis and sintering conditions are: heating from room temperature to 500°C at a heating rate of 0.5°C / min and maintaining for 6 hours; heating from 500°C to 1200°C at a heating rate of 3°C / min and maintaining for 10 hours to obtain an aluminosilicate ceramic carrier.

[0178] (3) Using silica sol (40wt% SiO2, Qingdao Junqiang New Materials Co., Ltd.) and aluminum sulfate (99wt%, Innochem) as the silicon source and aluminum source, respectively, and tetrapropylammonium hydroxide (TPAOH, 25wt%, Innochem) as the template, the silicon source, aluminum source, template and sodium hydroxide are added into water and mixed to obtain a crystallization mother solution, wherein the molar ratio of each raw material, i.e., SiO2:Al2O3:template:Na2O:H2O, is 1:0.01:0.06:0.2:40. The above mixture is crystallized at 170°C for 7 hours to obtain a crystallization incubation solution.

[0179] (4) placing the aluminosilicate ceramic carrier in a crystallization incubation solution, wherein the carrier: crystallization incubation solution mass ratio is 1:10, and hydrothermally crystallizing the carrier and crystallization incubation solution mixture at 170°C for 24 hours. After the hydrothermal crystallization is completed, the hydrothermal crystallization product is cooled, separated, washed, dried at 100°C for 4 hours, and calcined at 550°C for 5 hours to obtain a 3D printed molecular sieve catalyst.

[0180] (5) placing the sodium molecular sieve catalyst in an ammonium salt solution for ammonium exchange, wherein the mass ratio of the sodium molecular sieve catalyst to the ammonium salt solution is 1:10, the ammonium salt is ammonium chloride, the mass fraction of ammonium chloride in the ammonium salt solution is 10%, the ammonium exchange temperature is 80° C., the reaction time is 1 h, and the exchange is repeated 3 times. After the ammonium exchange is completed, the solid product obtained after the ammonium exchange is dried at 100° C. for 4 hours and calcined at 550° C. for 2 hours to obtain a hydrogen molecular sieve catalyst.

[0181] (6) The hydrogen-type molecular sieve catalyst is impregnated in a metal nickel salt solution, wherein the mass ratio of the hydrogen-type molecular sieve catalyst to the metal nickel salt solution is 1:0.51, the metal nickel salt is nickel acetate, and the mass fraction of the metal nickel salt is 11.5%. The impregnation conditions are: impregnation in a Schlenk tube, vacuuming at 25° C. for 4 hours, and the vacuum degree is -0.08 MPa. The solid product obtained after the impregnation is then dried at a temperature of 90° C. for 6 hours and calcined at 500° C. for 4 hours.

[0182] Test Example 1

[0183] The mass percentage of ZSM-5, the particle size of the molecular sieve, and the micropore volume and mesopore volume in the 3D printed molecular sieve catalysts prepared in the examples and comparative examples are shown in Table 1.

[0184] Table 1 Properties of the molecular sieve samples obtained in the examples and comparative examples

[0185]

[0186] Test Example 2

[0187] The properties of the metal nickel in the molecular sieve catalysts prepared in the examples and comparative examples were tested, and the results are shown in Table 2.

[0188] Table 2

[0189]

[0190]

[0191] From the results in Table 2, it can be seen that the metal nickel particles in the 3D printed molecular sieve catalyst prepared in the embodiment have a smaller particle size, and the particle size of the metal nickel particles is larger than the micropores of the molecular sieve, indicating that the metal nickel particles have not entered the interior of the molecular sieve framework and have not caused damage to the molecular sieve pore framework.

[0192] Test Example 3 Catalytic Activity Test of 3D Printed Molecular Sieve Catalyst

[0193] The 3D printed molecular sieve catalyst was placed in a fixed bed reactor with a reaction pressure of 0.15 MPa, a reaction temperature of 500 °C, and a feed weight hourly space velocity (WHSV) of 50 h -1 After the reaction, the liquid phase was collected by cooling, and the gas phase product was collected by draining gas collection method. The liquid phase product was analyzed by Agilent 7890B (HP-PONA column) chromatography, and the gas phase product was analyzed by Agilent 6890 chromatography.

[0194] The n-octane conversion rate was calculated according to the following formula: conversion rate = 1-(mass of n-octane in the liquid product / mass of n-octane raw material). The results are shown in Table 3.

[0195] The BTX mass fraction in the liquid product refers to the sum of the mass fractions of benzene (B), toluene (T) and xylene (X) in all liquid products.

[0196] Table 3

[0197]

[0198]

[0199] From the results in Table 3, it can be seen that the 3D printed molecular sieve catalyst prepared in the embodiment is used for catalytic cracking reaction, and the conversion rate is significantly higher than that of the comparative example under the condition of equivalent crystallinity. In addition, due to the dehydrogenation effect of metallic nickel, the mass fractions of high-value products benzene (B), toluene (T), and xylene (X) in the liquid phase product obtained in the embodiment are higher, indicating that the catalyst in the embodiment is more conducive to obtaining high-value products and can be used for the high-selectivity preparation of aromatics.

[0200] The catalytic cracking reaction was carried out using the pure molecular sieve-nickel catalyst of Comparative Example 3, and the conversion rate was also significantly lower than that of the embodiment under the same reaction conditions.

[0201] Compared with traditional molecular sieve powder, the 3D printed ZSM-5 molecular sieve catalyst prepared by the present invention is easy to separate and recover from the synthetic solution, the synthesis process has low equipment requirements, and has high catalytic activity. Therefore, the present invention has a good application prospect.

[0202] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a 3D printed molecular sieve catalyst, characterized in that: The method comprises the following steps: (1) providing an aluminosilicate photosensitive resin slurry containing aluminosilicate and a photosensitive resin, and then performing 3D printing to obtain an aluminosilicate ceramic body; (2) sintering the aluminosilicate ceramic body to obtain an aluminosilicate ceramic carrier; (3) crystallizing a crystallization mother solution containing a silicon source, an aluminum source, a template, an alkali source and water to obtain a crystallization incubation solution; (4) hydrothermally crystallizing the aluminosilicate ceramic support in a crystallization incubation solution, and then first calcining the solid product obtained by the hydrothermal crystallization to obtain a sodium-type molecular sieve catalyst; (5) exchanging the sodium-type molecular sieve catalyst with ammonium to obtain a hydrogen-type molecular sieve catalyst; (6) The hydrogen-type molecular sieve catalyst is impregnated with a metal nickel salt solution, and then the solid product obtained by the impregnation is subjected to a second calcination to obtain a 3D printed molecular sieve catalyst.

2. The method according to claim 1, wherein: The aluminosilicate comprises silicon-based powder and auxiliary powder, wherein the mass percentage of silicon-based powder on a dry basis is 35-65%, preferably 45-60%, and the mass percentage of auxiliary powder on a dry basis is 35-65%, preferably 40-55%; Preferably, the silicon-based powder is selected from at least one of silicon dioxide, white carbon black and diatomaceous earth; Preferably, the auxiliary powder is selected from at least one of kaolin, metakaolin, bentonite and montmorillonite.

3. The method according to claim 1 or 2, wherein: The mass ratio of the aluminosilicate to the photosensitive resin is 0.5-1:1, preferably 0.6-0.9:1; Preferably, the raw materials of the photosensitive resin include 1-5% of photoinitiator, 30-65% of prepolymer, and 30-65% of monomer by mass percentage, preferably include 1.5-4% of photoinitiator, 35-60% of prepolymer, and 37-62% of monomer by mass percentage; Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and isopropylthioxanthone; Preferably, the prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer; Preferably, the monomer is selected from at least one of 1,6-hexanediol diacrylate, tripropylene glycol diacrylate and trimethylolpropane triacrylate.

4. The method according to any one of claims 1 to 3, wherein: The conditions for 3D printing include: the light curing exposure power is 0.5-5mW / cm 2 , the exposure time of the first layer is 15-30s, the exposure time of other layers is 5-15s, and the thickness of a single layer of light curing is 20-100μm; Preferably, the cross-section of the aluminosilicate ceramic body is 0.5-15 cm; Preferably, the aluminosilicate ceramic carrier has a multi-porous self-supporting three-dimensional structure, and more preferably has a self-supporting three-dimensional structure with parallel radial and axial interconnected pores.

5. The method according to any one of claims 1 to 4, wherein: The sintering conditions in step (2) include: a temperature of 1100-1300° C. and a time of 5-20 hours; Preferably, the method further comprises pyrolyzing the aluminosilicate ceramic body before sintering, and the pyrolysis conditions include: temperature of 350-550° C. and time of 5-15 hours.

6. The method according to any one of claims 1 to 5, wherein: In the crystallization mother solution, the aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and the alkali source is calculated as Na2O, and the molar ratio of SiO2:Al2O3:template:Na2O:H2O is 1:(0.003-0.03):(0.05-0.25):(0.05-0.3):(30-55), preferably 1:(0.005-0.025):(0.08-0.2):(0.08-0.25):(35-50); Preferably, the silicon source is silica sol and / or tetraethyl orthosilicate; and / or, the aluminum source is selected from at least one of aluminum sulfate, aluminum isopropoxide and aluminum trichloride; and / or, the template is an organic amine microporous template for preparing ZSM-5.

7. The method according to any one of claims 1 to 6, wherein: The crystallization conditions in step (3) include: a crystallization temperature of 155-185° C., preferably 165-180° C., and a crystallization time of 3-10 h, preferably 4-9 h.

8. The method according to any one of claims 1 to 7, wherein: In step (4), the mass ratio of the aluminosilicate ceramic carrier to the crystallization incubation solution is 1:6-20, preferably 1:8-15, based on their respective total mass; Preferably, the conditions of the hydrothermal crystallization include: a crystallization temperature of 155-185° C., preferably 165-180° C., a crystallization time of 12-40 h, preferably 15-35 h; Preferably, the first calcination conditions include: a temperature of 500-600° C. and a time of 4-8 hours.

9. The method according to any one of claims 1 to 8, wherein: In step (5), the conditions for the ammonium exchange include: a temperature of 60-90° C., preferably 70-80° C., and a time of 0.5-3 h, preferably 1-2 h; Preferably, the number of ammonium exchanges is 2-4 times; Preferably, the mass ratio of the sodium molecular sieve catalyst to the ammonium salt solution is 1:8-20, preferably 1:10-15; Preferably, the ammonium salt is ammonium chloride and / or ammonium sulfate; Preferably, the mass fraction of the ammonium salt in the ammonium salt solution is 5-30%, preferably 10-20%.

10. The method according to any one of claims 1 to 9, wherein: In step (6), the immersion conditions include: temperature of 20-30° C., time of 1-5 hours, and vacuum degree of -0.05 to -0.1 MPa; Preferably, the mass ratio of the hydrogen-type molecular sieve catalyst carrier to the metal nickel salt solution is 1:0.06-1.29, preferably 1:0.25-1.02; Preferably, the amount of the hydrogen-type molecular sieve catalyst and the metal nickel salt solution is such that the mass percentage of nickel in the prepared 3D printed molecular sieve catalyst is 0.5-10%, preferably 2-8%; Preferably, the metal nickel salt is an organic nickel salt and / or an inorganic nickel salt, preferably at least one selected from nickel nitrate, nickel chloride and nickel acetate; Preferably, the mass fraction of the metal nickel salt in the metal nickel salt solution is 5-20%, preferably 10-15%.

11. A 3D printed molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 10; Preferably, the 3D printed molecular sieve catalyst comprises 20-55% by mass of ZSM-5 molecular sieve; Preferably, the ZSM-5 molecular sieve is distributed on the surface of the 3D printed molecular sieve catalyst and exists in the form of micron particle aggregates, and preferably the average particle size of the micron particles is 1-5 microns; Preferably, in the 3D printed molecular sieve catalyst, the mass percentage of nickel is 0.5-10%, preferably 2-8%; Preferably, the micropore volume of the 3D printed molecular sieve catalyst is 0.04-0.1 cm 3 / g; mesopore volume is 0.04-0.09cm 3 / g.

12. Use of the 3D printed molecular sieve catalyst prepared by the method according to any one of claims 1 to 10 or the 3D printed molecular sieve catalyst according to claim 11 in a catalytic cracking reaction.

Citation Information

Patent Citations

  • Hierarchical structure ZSM-5 molecular sieve containing lanthanum and nickel or / and zinc , and preparation method and application thereof

    CN113042094A

  • Molecular sieve supported metal catalyst and preparation method thereof

    CN113441175A

  • High- silica alumina ratio small- crystal grain Y zeolite catalytic cracking catalyst and preparation method thereof

    CN102553630A

  • 3D printing titanium oxide ceramic material and preparation method thereof

    CN106699111A

  • Preparation of ZSM-5 molecular sieve catalyst film for inner modification of metal channels as well as catalyst film and application thereof

    CN106881147A

Cited By

  • Additive manufacturing high-precision collapsible ceramic shell

    CN120984815A